Management of infants born with severe neonatal alloimmune thrombocytopenia: the role of platelet transfusions and intravenous immunoglobulin. Issue 3 (19th July 2013) - Bakchoul, Tamam; Bassler, Dirk; Heckmann, Matthias; Thiele, Thomas; Kiefel, Volker; Gross, Isabel; Arnold, Donald M.; DiTomasso, Julie; Smith, James W.; Paes, Bosco; Greinacher, Andreas
<x xml:space="preserve">Abstract</x> Background Neonatal alloimmune thrombocytopenia (NAIT) is a fetomaternal incompatibility most commonly induced by maternal anti‐HPA‐1a alloantibodies. Transfusion of immunologically compatible platelets (PLTs) to prevent cerebral hemorrhage, the most severe complication in affected newborns, is usually recommended. Such PLT concentrates, however, are often not readily available. Study Design and Methods The efficacy of random‐donor PLT transfusions and intravenous immunoglobulin (IVIG) for the management of 17 neonates across four centers with unexpected, severe NAIT was evaluated. Neonates were treated with random‐donor PLTs alone (n = 7), random‐donor PLTs with IVIG (n = 8), or matched HPA‐1bb PLTs (n = 2). Results All but one patient (treated with random PLTs and IVIG) achieved a posttransfusion PLT count of higher than 30 × 109/L after the first PLT transfusion. The PLT count remained higher than 30 × 109/L for longer than 24 hours in five of seven, seven of eight, and two of four newborns who received random‐donor PLTs alone, random‐donor PLTs with IVIG, or matched HPA‐1bb PLTs, respectively. None of the newborns developed major bleeding or intracranial hemorrhage. IVIG did not appear to improve either posttransfusion PLT counts or total PLT transfusion requirements. Conclusion Transfusion of random‐donor PLTs alone was effective at correcting critically low PLT counts and should be considered as first‐line treatment of newborns with unexpected severe NAIT.